Life-cycle cost analysis of SMA pavements and SMA application guidelines - Titus-Glover, Leslie; Von Quintus, Harold L.; Smith, Kelly L.; Stanley, M.; Rao, S. (Wisconsin Highway Research Program, 2006)
The objective of this research project was to provide a comparative cost analysis of pavements constructed using stone matrix asphalt (SMA) mixtures versus those built with Wisconsin Department of Transportation's (WisDOT?s) conventional hot-mix asphalt (HMA) mixtures, based on parallel life-cycles (inclusive of any required maintenance) and resultant performance. The research entailed a thorough evaluation of SMA and conventional HMA mixture performance on Wisconsin highways, collection and review of SMA and conventional HMA unit costs, and full-scale life-cycle costing to determine the cost-effectiveness of SMA pavements. Performance analysis, consisting of Pavement Distress Index (PDI) and International Roughness Index (IRI) threshold-based life projections combined with survival analysis techniques, resulted in SMA and HMA overlay service life estimates when placed on three groups of like pavements: (1) low-volume asphalt pavements on U.S./State routes, (2) high-volume jointed reinforced concrete (JRC) pavements on Interstate/U.S. routes, and (3) moderate-volume JRC pavements on U.S./State routes. Based on the results of the performance analysis, pavement life-cycle models were developed for SMA and HMA overlays corresponding to each group. Using the life-cycle models and historical-based best estimates of pay item unit costs, deterministic and probabilistic life-cycle cost analyses (LCCAs) were conducted. For group 1 overlay applications, SMA was found to be more cost-effective than conventional HMA, leading to the recommendation that SMA mixture use under this scenario be considered on a case-by-case basis. For group 2 and 3 overlay applications, the reverse was observed, with HMA found to be more cost-effective. However, a similar recommendation for SMA use under these scenarios was given, based on indications that the SMA overlays examined in the study were placed on rougher (possibly more deteriorated) pavements.
116 p.
Keywords: Cost effectiveness; Hot mix paving mixtures; Asphalt pavements; Concrete pavements; Wisconsin; Pavement performance; Unit costs; Overlays (Pavements); Life cycle costing; Pavement distress; Stone matrix asphalt; Service life